Predictors of changes in suicidality in multiple sclerosis over time. (May 2014) - Flood, Sara; Foley, Frederick W.; Zemon, Vance; Picone, MaryAnn; Bongardino, Matthew; Quinn, Helen
Abstract Purpose: Studies show that suicidality is greater in persons with multiple sclerosis (MS) than in the general population. In this study, we evaluated the consistency of suicidality over time in patients with MS. Method: Participants were patients (n = 344) at an outpatient clinic at a large medical center in New Jersey. Longitudinal data was collected as part of an ongoing research project. Binary logistic regression examined the effect of gender, age, depression and disability on level of suicidality at Time 1 versus Time 2. Results: Baseline depression and change in level of depression significantly predicted level of suicidality at Time 2, while demographic variables, baseline disability, change in level of disability, and the interaction between change in depression and change in disability over time did not. Conclusions: Interventions aimed at evaluating and monitoring depression over time should be considered in order to reduce the risk of suicidality. Implications for Rehabilitation Due to the inconsistency and unpredictability of MS, depression should be assessed routinely. Given the high prevalence of depression and suicidality in MS, mental health services should be available and encouraged by healthcare providers treating individuals with MS.